Genetic characterization of resistance to stripe rust, leaf rust, Karnal bunt and cereal cyst nematode in a multiple disease resistant wheat stock W8627 - Virdi, Reenu; Mavi, G.S.; Bala, Ritu; Sohu, V.S.; Bains, N.S.; Kaur, Daman Jeet; Sharma, Indu (The Indian Journal of Genetics and Plant Breeding, 2016)
Genetic analysis of multiple disease resistance was carried out in segregating populations of bread wheat line W8627 and PBW343 against stripe rust (Puccinia striiformis), leaf rust (Puccinia triticina), Karnal bunt (Tilletia indica) isolates and cereal cyst nematode (Heterodera avenae). Seedling response of W 8627, PBW 343 and F1 against 78S84 race of Puccinia striiformis, 77-5 race of P. triticina reflected that the wheat line W8627 possessed seedling resistance genes against both the races. Based on the segregation pattern of F2 generation and F3 families, two complementary recessive genes for resistance to 78S84 race of Puccinia striiformis and one recessive gene each for resistance to 77-5 race P. triticina, mixture of Tilletia indica isolates and Ha 41 biotype of H. avenae were identified. Co-segregation studies revealed no linkage between concerned resistance genes.